Price efficiency and trading behavior in limit order markets with competing insiders - Thomas Stöckl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
We study price efficiency and trading behavior in laboratory limit order markets with asymmetrically informed traders. Markets differ in the number of insiders present and in the subset of traders who receive information about the number of insiders present. We observe that price efficiency (i) is the higher the higher the number of insiders in the market but (ii) is unaffected by changes in the subset of traders who know about the number of insiders present. (iii) Independent of the number ofinsiders, price efficiency increases gradually over time. (iv) The insiders' information is reflected in prices via limit (market) orders if the asset's value is inside (outside) the bid-ask spread. (v) In situations where limit and market orders yield positive profits, insiders clearly prefer market orders, indicating a strong desire for immediate transactions.
Keywords: C92; D82; G12; G14; 330; insider; competition; asset market; price efficiency; trading behavior; experimental economics; Insiderhandel; Asymmetrische Information; Börsenkurs; Experimentelle Ökonomik; Theorie